دراسة نظرية لتقييم اداء محرك احتراق داخلي يعمل بنظام القدح وباستخدام مزيج من الكازولين مع الوقود الحاوي على الاوكسجين - نورالدين صالح خضر أحمد; عبدالرحمن حبو محمد الحبو (Journal of Engineering and Sustainable Development, 2019)
The aim of this research is to study the influence of added Oxygenated fuel (Ethanol or Methanol) at volume ratio values (5%) of each type to gasoline on Spark-Ignition Engine Performance including both the engine torque, brake specific fuel consumption, finally, brake thermal efficacy of engine and monitor the influence of this added fuel on pollutants quantity emitted included Carbon monoxide (CO), Nitrogen monoxide (NOx), A computer program was prepared in (VISUAL BASIC) to simulated the engine at different operating conditions included both the spark timing at ratio ranged from 5 btdc to 35 btdc with increasing 5 degrees in each iteration The compression ratio kept constant at (1:10) with equivalence ratio as well as engine speed of 2000 rpm.